Does the Quality of Education Today Depend on the Number of Students? - Ayubxon Bakhtiyorkhonovich Radjiev; Ibragimov Abdimalik Gapparovich; Kuchkinov Abdumalik Yuldoshevich; Muradov Ikrom Turdiboevich (International Journal on Integrated Education, 2022)
This article suggests that as a subproblem of improving the quality of education at school, the perception of the level of knowledge and professional skills of the teacher, as well as the abundance of students in the classroom are perceived as a subject problem that can negatively affect the quality of education.